2017
DOI: 10.1016/j.acap.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Communication in Primary Care for Spanish-Speaking and English-Speaking Parents

Abstract: Background and Objective Effective communication with primary care physicians is important yet incompletely understood for Spanish-speaking parents. We predicted lower satisfaction among Spanish-speaking compared with English-speaking Latino and non-Latino parents. Methods Cross-sectional analysis at 2-month well visits within the Greenlight study at 4 pediatric resident clinics. Parents reported satisfaction with 14 physician communication items using the validated Communication Assessment Tool (CAT). High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…In the acute care setting, limited English language proficient families have been found to perceive differences in nurse responsiveness that, in turn, affected their trust in nursing care (Radwin et al, 2013). Hispanic families and members of the health care team have both reported similar concerns about trust and the limited understanding, on the part of the families, of the complexities of health care situations when language barriers exist (Abbe et al, 2006;Fields et al, 2016;Flower et al, 2017). There is also evidence that cultural differences exist between Hispanic families and members of the health care team regarding the perception of urgency when clinical symptoms arise.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute care setting, limited English language proficient families have been found to perceive differences in nurse responsiveness that, in turn, affected their trust in nursing care (Radwin et al, 2013). Hispanic families and members of the health care team have both reported similar concerns about trust and the limited understanding, on the part of the families, of the complexities of health care situations when language barriers exist (Abbe et al, 2006;Fields et al, 2016;Flower et al, 2017). There is also evidence that cultural differences exist between Hispanic families and members of the health care team regarding the perception of urgency when clinical symptoms arise.…”
Section: Discussionmentioning
confidence: 99%
“…1 Latino children, including those in Spanish-speaking families, experience more delays in care, 2 are less likely to have a usual source of health care compared with other groups, 3 and receive fewer specialty referrals and testing. 4 Once children in Spanish-speaking families obtain care, satisfaction with communication is lower than for English-speaking groups, 5 and is reported to be less family-centered, as defined by principles that include respect and collaboration. 6 Health care access barriers and communication experiences may contribute to disparities, 7 and are therefore essential to understand.…”
mentioning
confidence: 99%
“…26 Interpreters are more likely to be available in hospitals or hospital-based clinics; even in these settings, visits for Spanish-speaking families were frequently conducted in English. 11,24 Machine translation is increasingly available and has the potential to address the challenges of language barrier in healthcare communications. 26 In addition to language barrier, our study showed that other factors at the caregiver-, provider-and system-level, contributed to the communication challenges experienced by SSP of CMC.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Spanish-speaking parents/caregivers (SSP) are less satis ed than English-speaking parents with healthcare provider communication about their children. 11,12 Children whose parents have LEP are more likely to experience delays in diagnosis, serious adverse events and longer hospitalizations, and are less likely to be assessed for pain or receive pain medication. [13][14][15][16] Because CMC have high healthcare utilization, the consequences of parental LEP are likely to be greater for these children compared to other children.…”
mentioning
confidence: 99%